2016
DOI: 10.3389/fmicb.2016.00709
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Mechanism of Plasmopara viticola RxLR Effectors on Suppressing Plant Immunity

Abstract: The RxLR effector family, produced by oomycete pathogens, may manipulate host physiological and biochemical events inside host cells. A group of putative RxLR effectors from Plasmopara viticola have been recently identified by RNA-Seq analysis in our lab. However, their roles in pathogenesis are poorly understood. In this study, we attempted to characterize 23 PvRxLR effector candidates identified from a P. viticola isolate “ZJ-1-1.” During host infection stages, expression patterns of the effector genes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 64 publications
5
73
0
Order By: Relevance
“…Suppression of Pattern Triggered Immunity (PTI) is a good marker to test the role of a given effector in virulence. It would be interesting to test whether P. halstedii RXLR or CRN effectors are able to suppress PTI induced by Phytophthora infestans infestin INF1, for example, as does the Phytophthora infestans Avr3A RXLR effector (Bos et al, 2006) and more recently, several RXLR from P. viticola (Xiang et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Suppression of Pattern Triggered Immunity (PTI) is a good marker to test the role of a given effector in virulence. It would be interesting to test whether P. halstedii RXLR or CRN effectors are able to suppress PTI induced by Phytophthora infestans infestin INF1, for example, as does the Phytophthora infestans Avr3A RXLR effector (Bos et al, 2006) and more recently, several RXLR from P. viticola (Xiang et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…After being secreted by oomycetous pathogens, the RXLR effectors are transported to a range of subcellular localizations in plant cells, including the nucleus, cytoplasm, or plasma membrane, which often associates with their functions and/or mode of action (McLellan et al, 2013;Xiang et al, 2016). The study of subcellular localization of RXLR effectors from Phytophthora infestans revealed that the nucleocytoplasmic distribution in plant cells is the most common pattern (Wang et al, 2019a).…”
mentioning
confidence: 99%
“…B, see Supporting Information). The expression pattern of PvRXLR131 was similar to that of the second group of PvRXLRs (Xiang et al ., ), and these genes were highly expressed during the earlier infection stages. In addition, PvRXLR131 was successfully detected in 48 P. viticola isolates (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Functional genomic studies have been carried out to characterize RXLR effectors. Notably, suppression of host immunity seems to be a major function of most effectors, as was demonstrated in the model plant Nicotiana benthamiana by monitoring their ability to suppress elicitor‐triggered cell death or to enhance pathogen leaf colonisation and in the bacteria Pseudomonas syringae by assessing their ability to promote pathogen pathogenicity (Fabro et al ., ; Liu et al ., ; Wang et al ., , ; Xiang et al ., ). RXLR effectors target diverse pathways within the host cell to suppress plant immunity, such as preventing secretion of defence‐related proteases (Bozkurt et al ., ), reducing the accumulation of reactive oxygen species around invasion sites (Dong et al ., ), perturbing mitogen‐activated protein kinase (MAPK) pathways (King et al ., ), supporting or promoting the activity of negative immune regulators (Boevink et al ., ; Murphy et al ., ), suppressing RNA silencing and reducing accumulation of small RNAs (Qiao et al ., , ), and reprograming pre‐mRNA splicing (Huang et al ., ).…”
Section: Introductionmentioning
confidence: 97%